2021
DOI: 10.3389/fpsyt.2021.684653
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Attempts, Neurocognitive Dysfunctions and Clinical Correlates in Middle-Aged and Elderly Chinese Schizophrenia Patients

Abstract: Background: Suicide is a common and complex symptom of schizophrenia that may be related to clinical variables and neurocognitive function. This study aimed to investigate the associated correlates of suicide attempts in Chinese middle-aged and elderly inpatients with schizophrenia, including demographic and clinical characteristics and cognitive level, which has not yet been reported.Methods: A total of 426 schizophrenia inpatients were recruited for this study. Clinical symptoms were evaluated using the Posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 42 publications
1
7
0
Order By: Relevance
“…This is similar to the results of previous studies [ 20 , 21 ], and suggests that suicidal ideation among patients with SZ might not be related to neurocognitive function. However, the results of previous studies are inconsistent, and some studies [ 14 16 ] have reported that impaired neurocognition in patients with SZ is a risk factor for suicide while others suggest that the risk of suicide in patients with SZ increases with improved cognitive function [ 17 19 ]. Thus, given that the reported relationship between suicidal ideation and neurocognitive in patients with SZ is inconsistent, further prospective studies with larger samples are needed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is similar to the results of previous studies [ 20 , 21 ], and suggests that suicidal ideation among patients with SZ might not be related to neurocognitive function. However, the results of previous studies are inconsistent, and some studies [ 14 16 ] have reported that impaired neurocognition in patients with SZ is a risk factor for suicide while others suggest that the risk of suicide in patients with SZ increases with improved cognitive function [ 17 19 ]. Thus, given that the reported relationship between suicidal ideation and neurocognitive in patients with SZ is inconsistent, further prospective studies with larger samples are needed.…”
Section: Discussionmentioning
confidence: 99%
“…However, findings on the association between suicide risk and cognitive impairment in SZ have been inconsistent. Some studies [ 14 16 ] have reported that impaired neurocognition in patients with SZ is a risk factor for suicide, while others have reported a positive relationship between suicidal risk and improved cognitive function [ 17 19 ], or no association between the two variables [ 20 , 21 ]. Neurocognitive decline is often associated with aging [ 22 ], so the current study focused on young adults aged 18–44 years.…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between neurocognition and suicidal ideation is heterogeneous in previous studies. Some studies insisted that preserved neurocognition is associated with the suicidality [ 15 , 21 , 22 ], while the other studies insisted that there is no correlation between neurocognition and suicidality [ 23 , 24 , 59 ]. There are various reasons for these heterogeneous results, such as patient selection bias, different definitions of suicidal categories and different measurement tools for neurocognition.…”
Section: Discussionmentioning
confidence: 99%
“…Neurocognition impairment is an essential feature of SZ [ 20 ]. Previous studies have reported that preserved neurocognitive function are related to suicidality in SZ patients [ 15 , 21 , 22 ]. However, other studies reported that suicidality is not correlated with neurocognitive function in SZ patients [ 23 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation